Characterization of multi-type pore structure and fractal characteristics of the Dalong Formation marine shale in northern Sichuan Basin. Issue 22 (16th November 2020) - Zhang, Jizhen; Li, Xianqing; Zou, Xiaoyan; Li, Jian; Xie, Zengye; Wang, Feiyu
ABSTRACT: Pore structure and fractal characteristics are the discussion hotspots in the theoretic field of shale gas reservoir, however, less attention has been paid to the quantitatively characterization of different types of shale pores. Various types of micro-pores developed in the Dalong shales, including inter-particle pore, intra-particle pore, inter-crystal pore, dissolved pore, organic matter (OM) pore, and micro-fracture. These pores are dominated by nanopores with the size diameters of < 10 and 30–600 nm. The shale pore structures have the high complexity and heterogeneity, with the fractal dimensions of 2.45–2.80, which have good positive relationship with the porosity. TOC contents and brittle minerals dominate the development of OM pore and inorganic pores, respectively. OM pores are the most significant contributor to the complexity and heterogeneity of pore structures. Dalong shales have good shale gas content and hydrocarbon generating potential for commercial exploration of shale gas resources. Shale gas is mainly stored in shale pore networks, while the pores within clay mineral layers play the dominate role in adsorbing shale gas. Large amount of OM pores in shales generating from the hydrocarbon generation progress from kerogen support the shale gas-generating potential.